Adherence, reliability, and variability of home spirometry telemonitoring in cystic fibrosis - Beaufils, Fabien; Enaud, Raphaël; Gallode, François; Boucher, Grégory; Macey, Julie; Berger, Patrick; Fayon, Michael; Bui, Stéphanie (Frontiers in Pediatrics, 2023)
Introduction Forced spirometry is the gold standard to assess lung function, but its accessibility may be limited. By contrast, home spirometry telemonitoring allows a multi-weekly lung function follow-up but its real-life adherence, reliability, and variability according to age have been poorly studied in patients with CF (PwCF). We aimed to compare real-life adherence, reliability and variability of home spirometry between children, teenagers and adults with CF. Methods This real-life observational study included PwCF followed for six months in whom lung function (i.e, forced expiratory volume maximum in 1 s (FEV1), forced vital capacity (FVC), forced mid-expiratory flow (FEF) and FEV1/FVC ratio) was monitored by both conventional and home spirometry between July 2015 and December 2021. The adherence, reliability and variability of home spirometry was assessed in all PwCF and compared between children (<12years old), teenagers (12–18 years old) and adults. Results 174 PwCF were included (74 children, 43 teenagers and 57 adults). Home spirometry was used at least one time per week by 64.1 ± 4.9% PwCF, more frequently in children and teenagers than in adults (79.4 ± 2.9%, 69.2 ± 5.5% and 40.4 ± 11.5% respectively). The reliability to conventional lung function testing was good for all assessed parameters (e.g., FEV1: r = 0.91, p < 0.01) and the variability over the 6 months of observation was low (FEV1 coefficient of variation = 11.5%). For each parameter, reliability was better, and the variability was lower in adults than in teenagers than in children Conclusion Home spirometry telemonitoring appears to be a reliable tool for multi-weekly lung function follow-up of PwCF.